A reconstituição de experiências após um acidente de trabalho: mapas de percurso como instrumento de análise - Cláudia Pereira; Vanessa Rodrigues (Universidade do Porto, 2018)
This paper aims at exploring a methodological instrument - the accident journey charts -, depicting their structure and the challenges and potential related to their use. The accident journey charts were designed under the scope of a research which focused on the analysis of the circumstances and consequences the work accidents have on the individuals and on the back-to-work process. Additionally, the accident journey charts took an exploratory role in looking at processes of reconstruction of experiences after a work accident, focusing on the institutional path the injured people had to follow. Their use, within the study, was determinant to reveal and depict the paths and journeys of the injured workers after an accident, through the temporal reconstruction of a story and a health event - the accident. It also contributed to a better understanding of the accident's impact on the injured workers' life (on the institutional path, on the interactions that took place, and on the feelings and emotions they have been through).